2016
DOI: 10.1127/entomologia/2016/0131
|View full text |Cite
|
Sign up to set email alerts
|

A study on parasitoids of the hoverflies (Dipt.: Syrphidae) and their natural effects on them in organic aphid infested lettuce farms of Yazd Province, Iran

Abstract: The hoverflies (Dipt.: Syrphidae) are known as important biological control agents of hemipterans in agricultural ecosystems. The study was conducted to evaluate the parasitism of larvae of hoverflies on organic aphid infested lettuce farms in Yazd province, Iran during 2011. Five heads of lettuce were sampled and inspected in three times from late winter to the harvesting time. A total of 258 syrphid larvae were collected and reared under room temperature. Two species of Syrphidae, Eupeodes corolla Fabricius,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Whether parasitoids are likely to be a significant problem in captive rearing environments is not yet known. However, if following a mass‐rearing practice, parasitoidy by wasps may be reduced by releasing syrphid larvae at third‐instar only because the feeding capacity of larvae is impacted less and the survival rate may be higher …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether parasitoids are likely to be a significant problem in captive rearing environments is not yet known. However, if following a mass‐rearing practice, parasitoidy by wasps may be reduced by releasing syrphid larvae at third‐instar only because the feeding capacity of larvae is impacted less and the survival rate may be higher …”
Section: Discussionmentioning
confidence: 99%
“…Parasitoid wasps can also be problematic, mainly if they are brought in with collected syrphid larvae. Ichneumonid wasps are the principal parasitoids of syrphid larvae, although members of several other Hymenoptera families including wasp species from Pteromalidae and Encyrtidae have been identified and studied . At least one study has reported syrphid larval defence mechanisms against parasitoid attacks, though quantification of the efficiency of these actions on avoiding parasitism has not been undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution in Iran: Alborz, Guilan, Mazandaran, Qazvin, Tehran (Mohammadi-Khoramabadi et al, 2013b), Chaharmahal and Bakhtiari (Nourbakhsh et al, 2008), Isfahan (Barahoei et al, 2015;Rakhshani et al, 2010), Kerman (Bakhtiari et al, 2014), Sistan and Baluchistan (Barahoei et al, 2013), Yazd (Mohammadi-Khoramabadi et al, 2016b).…”
Section: Diplazon Laetatorius (Fabricius 1781)mentioning
confidence: 99%
“…Many studies in recent years have increased our knowledge on the fauna, distribution (Amiri et al, 2015a(Amiri et al, , 2015b(Amiri et al, , 2016a(Amiri et al, , 2016bHooshyar et al, 2018;Jahan et al, 2016;Mahyabadi et al, 2016;Mohammadi-Khoramabadi & Talebi, 2013;Mohammadi-Khoramabadi et al, 2013a;2013b;Mohammadi et al, 2020;Riedel et al, 2019a;Sarafi et al, 2015;Shirzadegan et al, 2017Shirzadegan et al, , 2018aShirzadegan et al, , 2018b and bioecology of these important and abundant parasitoid wasps in forest, range and agricultural ecosystems of Iran (Akbarzadeh-Shoukat, 2012;Fathi et al, 2012;Kamangar et al, 2017;Mehrnejad & Basirat, 2009;Mohammadi-Khoramabadi et al, 2016aPourhaji et al, 2016;Shamszadeh et al, 2015). Northwest of Iran is of great importance both in terms of animal genetic resources, which contains five national park and protection areas (Hanson et al, 2009;Zehzad et al, 2002) and in terms of its potency of agricultural products (Ebadzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Diplazontinae species are solitary, koinobiont endoparasitoids of the family Syrphidae Latreille, 1802 (Insecta, Diptera) and all but one genus (Bioblapsis Förster, 1869) which attack a fungus-feeding syrphid, appear to be specialized on the host aphids (Johansson, 2020). These wasps are the main biotic factors that reduce the population and abundance of syrphid flies (Mohammadi-Khoramabadi et al, 2016b). Diplazon laetatorius (Fabricius, 1781) is the most common and widespread species parasitizing about 40 Journal of Insect Biodiversity and Systematics 2024  10 (in press) species of Syrphidae around the world (Broad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%